Proteomic analysis of macrophage in response to Edwardsiella tarda-infection. (October 2017) - Qin, Lei; Li, Fuhou; Wang, Xingqiang; Sun, Yuying; Bi, Keran; Gao, Yingli
Abstract: Edwardsiella tarda is an important facultative intracellular pathogen infecting a wide range of host from fish to humans. This bacterium could survive and replicate in macrophages as an escape mechanism from the host defense. E. tarda -macrophage interaction is vital in determining the outcome of edwardsiellasis. To fully elucidate the pathogenesis of E. tarda, the differential proteomes of RAW264.7 cells in response to E. tarda -infection, were analyzed at different time points with two-dimensional gel electrophoresis (2-DE) followed by liquid-chromatography-tandem mass spectrometry (LC-MS/MS) identification. 26 altered proteins (18 up-regulated and 8 down-regulated proteins) were successfully identified, which are mainly involved in formation of phagosomes, macrophage microbicidal activity and anti-apoptosis of macrophage. Moreover, 6 corresponding genes of the differentially expressed proteins were quantified by quantitative real-time PCR (qPCR) to examine the transcriptional profiles. Western blot analysis further confirmed the differential expression of 5 proteins in the proteomic profiles. Based on these findings, we hypothesize that these differentially expressed proteins likely play a pivotal role in determining the course of E. tarda -infection. The result suggested that E. tarda could develop some strategies to achieve a successful intracellular lifestyle, including modulation of phagosome biogenesis, resistance to macrophage microbicidal agent and anti-apoptosis of macrophages. Thus, this work effectively provides useful and novel protein-related information to further understand the underlying pathogenesis of E. tarda -infection. Highlights: E. tarda could survive and replicate in macrophages as an escape mechanism from the host defense. Proteomic analysis of macrophages infected by E. tarda were conducted with 2-DE followed by LC-MS/MS. The differentially expressed proteins were confirmed by qPCR and Western blot. 18 up-regulated and 8 down-regulated proteins were successfully identified at different time points. These proteins are mainly involved in formation of phagosome, microbicidal activity and anti-apoptosis of macrophages.